Microsclerotia formation of the biocontrol fungus Cordyceps javanica IF-1106 and evaluation of its stress tolerance and pathogenicity - Li, Yihua; Li, Junmei; Cai, Xiaoxia; Gao, Meiyu; Diao, Hongliang; Xiang, Huiming; Zhou, Wenwen; Ma, Ruiyan (Frontiers in Microbiology, 2025)
IntroductionCordyceps javanica IF-1106 is an entomopathogenic fungus with a wide range of hosts. It produces microsclerotia in liquid media.MethodsThis study took a close observation of the microsclerotia formation process of C. javanica IF-1106 and described the surface characteristics of C. javanica IF-1106 microsclerotia. Secondly, the viability of microsclerotia under high temperature and ultraviolet radiation were determined. Thirdly, the microsclerotia were stored under different temperatures to assess storage stability. Finally, activity of microsclerotia against root-knot nematode and the influence on the plant growth of cucumber were investigated.Results and discussionSpores germinate quickly, and hyphal elements clump together, forming hydrophobic microsclerotia. The microsclerotia have 100% survival under 55°C and UV-B radiation of 3 J cm−2. Following such exposure, the microsclerotia are able to germinate and produce conidia. After 1 year of storage at either room temperature (25°C) or refrigeration (−80°C, −20°C, and 4°C), all the microsclerotia germinated and spore yield was more than 4 × 109 spores g−1. Finally, C. javanica IF-1106 microsclerotia showed ovicidal activity against root-knot nematode eggs, and a glasshouse pot trial indicated that control efficiency of microsclerotia against root-knot nematodes reached 92.6%, which improved the growth of the test cucumber plants. These attributes suggest that microsclerotia of this fungus can be applied as a biocontrol agent to control soil borne pest nematodes.